A study on relationship between pulsatile tinnitus and temporal bone pneumatization grade. Issue 7 (19th May 2019) - Tian, Shan; Fan, Xingyu; Wang, Yawei; Liu, Zhaohui; Wang, Lizhen
Abstract: Pulsatile tinnitus (PT) is a common symptom in otology. In some cases, the venous flow in the sigmoid sinus (SS) is the source of PT. It is suggested that the venous sound is propagated into the tympanic cavity through the air pathway of temporal bone air cells (TBAC). The hyperpneumatization of TBAC was hypothesized as a direct pathology of PT through amplifying the venous sound, but there is no quantitative analysis. This study aims to quantify the relationship between the venous sound amplification and the pneumatization grade of TBAC. The acoustic numerical simulation and statistical analysis were performed based on the radiology data of 21 pulsatile tinnitus patients. The TBAC of these patients were classified into hypopneumatization, normal pneumatization and hyperpneumatization grades according to three standards. The in vitro acoustic experiment was done as the validation of simulation. It is indicated that the SS standard is effective for the clinical evaluation of venous sound amplification. The TBAC amplifies the venous sound due to the acoustic resonance at the first mode frequency, regardless of the pneumatization grades. The normal pneumatic TBAC exhibits the highest sound amplification effect on the venous sound amongst the three grades, contributing mostly to PT, but would not induce PT without any other causes.